Innovation and Ontologies Structuring the Early Stages of Innovation Management - Bullinger, Angelika (Markt- und Unternehmensentwicklung Markets and Organisations, 2009)
Innovation requires a balanced amount of openness and structure, especially in its early phases. Ontologies as logical representations of knowledge bear the potential of bridging this obvious dilemma and provide a promising approach to significantly improve management during the early stages of the innovation process. Angelika C. Bullinger examines ontologies as an approach to modeling, analyzing and comparing the fuzzy front end of innovation management, in particular idea assessment and selection. She uses an extensive array of theories and methods, combining the knowledge bases of business administration and information systems. Starting from theoretical informatics, she elaborates, applies and tests a methodology for ontology development for use in business management. Based on empirical data, she models ontologically the moment of idea assessment and selection on a company-specific, industry-typical and generic level. Included are action-oriented implications for the implementation of the methodology in business reality.